Peningkatan Minat dan Kompetensi Bahasa Bali Melalui Pembelajaran Rekreatif dan Inovatif di SD Negeri 1 Tembuku - Agus Artana, I Komang; Wahyu Mahendra Bhujangga, I Putu; Sri Evita Damayanti , Ni Luh Ketut; Putu Pratiwi , Ni Luh; Purnama Cahyani , Ni Putu Anggita; Intan Lestari , Luh Made; Mira Kesuma , I Gusti Ayu Agung; Dea Juniarti , Komang; Laksmi Puspariani , Putu; Mahesa Ardana , I Ketut Arya; Sintya Pratiwi , Anak Agung Istri; Senia Remani , Ni Wayan; Pradnya Jayanti , Ni Made; Rai Surya Nata, Anak Agung Gede (Sevanam: Jurnal Pengabdian Masyarakat, 2026)
Balinese, which is the native language of Bali, is taught in schools (especially elementary schools) in Bali as a local content subject. As part of the education curriculum, Balinese language lessons are also studied by multicultural and multilingual students, especially in urban areas. Balinese language learning is generally less appealing to students who do not speak Balinese because, first, Balinese is not their first or second language, and Balinese is not very demanding in their lives. This lack of interest leads to a lack of competence in Balinese among students. To improve students' competence, especially their communicative competence, it is considered necessary to start a recreational learning process, which keeps students interested and enjoying the learning process so that they are motivated to study well and achieve good results. This paper explores the importance of recreational learning methods, in this case learning through stories, complete with role-playing, learning through songs and music, and learning through group activities and games. This model is also very effective in improving children's character.